2021
DOI: 10.21203/rs.3.rs-264950/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coronary Sinus Atrial Septal Defects in Adults over the Past 20 Years at New Tokyo Hospital: Case Series

Abstract: Background: Isolated coronary sinus atrial septal defect (ASD) is defined as a coronary sinus unroofed in the terminal portion without a persistent left superior vena cava and other anomalies. This defect is rare and part of a wide spectrum of unroofed coronary sinus syndromes. Recently, several reports have described this finding. We searched the hospital’s database to determine the incidence of this defect, and to raise awareness of this condition, we discussed the findings from five patients with coronary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The association of mitral damage and ASD of the coronary sinus is rarely described in the literature. In Sugimori's study, all five patients reported had mitral insufficiency concomitant with the interatrial septal defect [25]. Two lesional mechanisms of mitral regurgitation were found in this same series including prolapse of the anterior leaflet of the valve in one patient and dilatation of the annulus in the remaining patients.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The association of mitral damage and ASD of the coronary sinus is rarely described in the literature. In Sugimori's study, all five patients reported had mitral insufficiency concomitant with the interatrial septal defect [25]. Two lesional mechanisms of mitral regurgitation were found in this same series including prolapse of the anterior leaflet of the valve in one patient and dilatation of the annulus in the remaining patients.…”
Section: Discussionmentioning
confidence: 75%
“…A study of pulmonary and systemic pressures and flows by right catheterization was proposed for our case before the indication of closure. As pointed out in case studies reported in the literature regarding ASD closure: it appears that a Qp/Qs ≥ 1.5, a PVR level ≤ 3uW and a positive reversibility test could be contributory to a satisfactory operative outcome [25,26]. The effect of ASD closure on pulmonary pressure is sometimes difficult to predict.…”
Section: Discussionmentioning
confidence: 99%